The “Modus Vivendi, Trade and Clearing Agreement” Between the Republic of Lithuania and the Republic of Türkiye and Its Significance in the Context of Bilateral Relations - Rinkevičius, Šarūnas (Lietuvos istorijos studijos, 2024)
The “Modus Vivendi, Trade and Clearing Agreement” signed between the Republic of Lithuania and the Republic of Türkiye in 1939 is not only one of the milestones in their bilateral relations during the times of the First Lithuanian Republic; it marks the intensifying commercial relations between the states at the time, and also reflects the development of their bilateral relations during this period. The aim of the article is to analyze the context of the aforementioned agreement, explore the proces of its preparation and negotiations and assess its significance for the development of bilateral trade and relations, based on the documents that are held in three archives in the Republic of Türkiye – the Turkish Diplomatic Archive (DIAD), Turkish Republican Archive (BCA), and Turkish Ottoman Archive (BOA) – as well as the Lithuanian Central State Archive.